Finite element analysis predicts Ca2+ microdomains within tubular-sarcoplasmic reticular junctions of amphibian skeletal muscle - Oliver J. Bardsley (Nature Portfolio, 2021)
Abstract A finite element analysis modelled diffusional generation of steady-state Ca2+ microdomains within skeletal muscle transverse (T)-tubular-sarcoplasmic reticular (SR) junctions, sites of ryanodine receptor (RyR)-mediated SR Ca2+ release. It used established quantifications of sarcomere and T-SR anatomy (radial diameter $$d=220 \, \mathrm{n}\mathrm{m}$$ d = 220 n m ; axial distance $$w=12 \, \mathrm{n}\mathrm{m}$$ w = 12 n m ). Its boundary SR Ca2+ influx densities, $${J}_{\mathrm{influx}}$$ J influx , reflected step impositions of influxes, $$\it {\Phi }_{\mathrm{influx}}={J}_{\mathrm{influx}}\left(\frac{\pi {d}^{2}}{4}\right),$$ Φ influx = J influx π d 2 4 , deduced from previously measured Ca2+ signals following muscle fibre depolarization. Predicted steady-state T-SR junctional edge [Ca2+], [Ca2+]edge, matched reported corresponding experimental cytosolic [Ca2+] elevations given diffusional boundary efflux $$\it \it {\Phi }_{\mathrm{efflux}}=\frac{D [ {{{\mathrm{Ca}}^{2+}}}]_{\mathrm{edge}}}{\lambda } (\pi dw),$$ Φ efflux = D [ Ca 2 + ] edge λ ( π dw ) , established cytosolic Ca2+ diffusion coefficients $$(D = 4 \times {10}^{7} \mathrm{nm}^{2}/\mathrm{s})$$ ( D = 4 × 10 7 nm 2 / s ) and exit length $$\lambda = 9.2 \, \mathrm{n}\mathrm{m}$$ λ = 9.2 n m . Dependences of predicted [Ca2+]edge upon $${J}_{\mathrm{influx}}$$ J influx then matched those of experimental [Ca2+] upon Ca2+ release through their entire test voltage range. The resulting model consistently predicted elevated steady-state T-SR junctional ~ µM-[Ca2+] elevations radially declining from maxima at the T-SR junction centre along the entire axial T-SR distance. These [Ca2+] heterogeneities persisted through 104- and fivefold, variations in D and w around, and fivefold reductions in d below, control values, and through reported resting muscle cytosolic [Ca2+] values, whilst preserving the flux conservation ( $$\it \it {\Phi }_{\mathrm{influx}}={\Phi }_{\mathrm{efflux}})$$ Φ influx = Φ efflux ) condition, $${\left[\mathrm{C}{\mathrm{a}}^{2+}\right]}_{\mathrm{edge}}=\frac{\lambda {dJ}_{\mathrm{influx}}}{4Dw}$$ C a 2 + edge = λ dJ influx 4 D w . Skeletal muscle thus potentially forms physiologically significant ~ µM-[Ca2+] T-SR microdomains that could regulate cytosolic and membrane signalling molecules including calmodulin and RyR, These findings directly fulfil recent experimental predictions invoking such Ca2+ microdomains in observed regulatory effects upon Na+ channel function, in a mechanism potentially occurring in similar restricted intracellular spaces in other cell types.